A Model of Optimal Foreign Exchange Hedging Without Exchange Rate Projections - Kohlhagen, Steven W. (Journal of International Business Studies, 1978)
This article presents a technique for optimal hedging decisions for a general set of international financial problems, specifically within the context of a floating exchange rate regime. The techniques discussed are designed specifically to require neither exchange rate projections nor the specification of a utility function for the decision-maker. Rather, the decision-maker is encouraged to analyze the implications of a given financial strategy over a reasonable range of future exchange rates, choosing the strategy that best meets corporate financial goals in light of possible (and uncertain) exchange rate fluctuations.